2013
DOI: 10.1016/j.chiabu.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exposure to violence and victimization across life domains on adolescent substance use

Abstract: Objective This study uses longitudinal data from the Project on Human Development in Chicago Neighborhoods (PHDCN) to examine the effects of exposure to school violence, community violence, child abuse, and parental intimate partner violence (IPV) on youths’ subsequent alcohol and marijuana use. We also examine the cumulative effects of being exposed to violence across these domains. Methods Longitudinal data were obtained from 1,655 adolescents and their primary caregivers participating in the PHDCN. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 48 publications
(102 reference statements)
9
100
0
2
Order By: Relevance
“…Several studies have shown that the exposure of children and adolescents to violence or experiences of victimization has a significant correlation with drug abuse later in life (6,20). This group commonly initiates substance use earlier, uses multiple substances more frequently and at a higher rate (18,19), and develops substance-abuse-related problems more often (19).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that the exposure of children and adolescents to violence or experiences of victimization has a significant correlation with drug abuse later in life (6,20). This group commonly initiates substance use earlier, uses multiple substances more frequently and at a higher rate (18,19), and develops substance-abuse-related problems more often (19).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
“…Experiences of both direct and indirect victimization have been shown to influence later drug abuse among adolescents (22)(23)(24), although psychological abuse has a somewhat lower correlation with drug abuse as compared with physical and sexual abuse (1). The cumulative effect of poly-victimization is also related to more severe drug abuse (6,7,23), and adolescents who have been exposed to both physical and sexual abuse are at particularly high risk for drug abuse (1,7). Adolescents who witnessed community violence also exhibit higher rates of tobacco, alcohol, and drug use later in life (6,24).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
See 3 more Smart Citations